Analysis Of Achievement Guidance Of Martial Arts Sports In Pekalongan City - Ariyadi, Aris; Raharjo, Hermawan Pamot; Setiawan, Ipang (Universitas Negeri Semarang, 2025)
This research is motivated by the fact that martial arts competed in various competitions have not achieved the targets that have been set. This study aims to analyze the development of martial arts achievements in the city of Pekalongan. This study uses a qualitative method with an exploratory approach. Data sources come from KONI, sports coaches, and athletes, as well as supporting documents and the location of the research. Data were collected through observation, interviews, and documentation. Data validity techniques use source and method triangulation and are analyzed using SWOT analysis. The study results show the strength of martial arts achievements in Pekalongan, such as a well-organized development organization, structured and sustainable training programs, sufficient funding, and synergy between development elements. Weaknesses include inadequate facilities and infrastructure, the welfare of coaches and athletes not being guaranteed, the academic burden of athletes' interference with the consistency of training, and the monitoring system for athletes outside the region not being optimal. Opportunities for achievement achieved by athletes, Public and media support, Tiered development system, and Availability of certified coaches. Threats of Competition between clubs and coaches, fluctuating funding, policy changes and decentralization of sports, Lack of mental coaching support, and Lack of mechanisms for selection and distribution of aid. This study concludes that [martial arts sports coaching in Pekalongan City has the potential to develop through organizational structure, competent coaches, and targeted training programs. However, it is still constrained by funding, facilities, and welfare. Optimal management of opportunities and threats is needed to achieve sustainable coaching.